Effect of Surface-modified Nano-silica on the Mobility and Fraction of Cd in Contaminated Agricultural Soils. Issue 1 (2nd January 2020) - Wang, Yangyang; Zhan, Wenhao; Zheng, Kaixuan; Liu, Yidan; Zou, Xueyan; Zhang, Chaosheng; Ruan, Xinling
ABSTRACT: Cadmium (Cd) contamination in agricultural soils is a widespread problem in China. In situ stabilization has been considered as one of the appropriate methods in remediation of Cd-contaminated soils. Besides the stabilization efficiency, more information regarding the influences of the stabilizer on soil properties is also required. In the present research, surface-modified nano-silica (SMNS) was used to remediate Cd-contaminated agricultural soils. When the dosage of SMNS was at 1%, the diethylenetriaminepentaacetic (DTPA)-extractable Cd decreased from 1.32 mg/kg to 0.116mg/kg on the 180th day, with the stabilization efficiency of 91.21%. Meanwhile, the exchangeable and carbonate-bounded Cd decreased 69.26 and 48.39%, respectively. Correlation analyses implied that SMNS transferred the exchangeable and carbonate-bounded fractions of Cd to the residual fraction. Furthermore, the mobility of Cd in soil also decreased from 45.78 to 18.95%. Mechanism analysis revealed that Cd was adsorbed on SMNS mainly by -SH and -OH bonds. Besides that, the addition of SMNS had negligible influences on soil properties. These results indicate that SMNS has great advantages and potential in stabilizing Cd-contaminated agricultural soils.